Relationship between cyclic and non-cyclic force-velocity characteristics in BMX cyclists - Gross, M.; Gross, T. (Sports, 2019)
Especially for bicycle motocross (BMX) cyclists, transfer of muscular force-velocity (Fv) characteristics between common strength training exercises and cycling is important. This study investigated the relationship between Fv characteristics in a common training exercise (squat jumps) and a sport-specific task (cycling) in high-level BMX racers by exploring the degree to which Fv and torque-cadence (Tc) characteristics correspond. Twelve BMX racers performed an Fv (multiple loaded squat jump) and two Tc tests (ramp starts and flat-ground sprints). Results revealed very large correlations between F0 and Tor0 start (r = 0.77) and between Pmax jump and Pmax start (r = 0.85). On the other hand, the relationships between v0 and Cad0 start (r = -0.25) and between SFv and STc start (r = -0.14) were small and negative. Similar results were observed for sprints. Based on dichotomous classifications (greater or less than group median), several discrepancies occurred, particularly for the profile slopes and high-speed variables. Thus, we recommend performing both jump-based and cycling-specific Fv testing. Of additional note, Tc characteristics on flat ground were similar to, but slightly different from those on the start ramp. Therefore, where possible, Tc tests should be carried out on a ramp.